Struktur Pasar dalam Perspektif Islam: Kajian Mikro Ekonomi Terhadap Prinsip Keadilan dan Transparansi - Nurul Aini Harahap; Suci Indah Triani; Reni Ria Armayani Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Market structure is a fundamental element in microeconomic studies that influences the interaction between business actors and consumers. From an Islamic perspective, market structure is not only assessed based on efficiency and competition, but also prioritizes the values of justice and transparency. This study aims to examine how Islamic economic principles are applied in various forms of market structures and their implications for the behavior of economic actors. With a qualitative approach based on literature studies, this article examines the concept of justice ('adl) and openness of information as the main pillars in forming a healthy market according to Islamic law. The results of the study show that Islam encourages the creation of a free market but is still ethically controlled so that there are no practices of exploitation, price manipulation, or misleading information. This finding strengthens the importance of regulations that are in line with Islamic values in forming a sustainable economic system that is oriented towards the common good.